Analysis of the Conditions for the Emergence of Spatially Inhomogeneous Structures of Light Waves in Optical Information Transmission Systems - Evgenii P. Kubyshkin; Vladimir A. Kulikov (Моделирование и анализ информационных систем)
A model of distributed information carriers in the form of stable spatially inhomogeneous structures in optical and fiber-optic communication systems is considered. We study the conditions for the occurrence of such stable spatially inhomogeneous structures of the light wave of the generator of optical radiation. The formation of inhomogeneous structures that occur in a plane orthogonal to the direction of wave propagation is provided by a thin layer of nonlinear medium and a two-dimensional lagging feedback loop with the rotation operator of the spatial coordinates of the light wave in the emission plane of the optical generator. In the space of the main parameters of the generator (a control parameter, the angle of rotation of the spatial coordinates, the magnitude of the delay), the areas of generation of stable spatially inhomogeneous structures are constructed, the mechanisms of their occurrence are analyzed.